The effect of methylphenidate on pain perception thresholds in children with attention deficit hyperactivity disorder - Abdullah Bozkurt; Selin Balta (BMC, 2023)
Abstract Background Pain perception is important in children with attention deficit hyperactivity disorder (ADHD) since they are more likely to experience painful events due to increased accident rates. The aim of this study is to contribute to the literature concerning the relationship between ADHD diagnosis, methylphenidate (MPH) therapy, and pain thresholds, since findings regarding the change in pain perception in children with ADHD are scarce and inconsistent. Methods Children aged 8-13 years constituted both the ADHD group (n = 82) and the healthy controls (n = 41). The ADHD group was divided into two subgroups, ADHD without MPH (not treated pharmacologically) and ADHD with MPH (treated pharmacologically for at least three-months). The Conners' Parent Rating Scale-Revised: Short Form was employed to assess ADHD, a visual analog scale was applied to evaluate chronic pain severity, and a manual pressure algometer was used to assess pain thresholds. Result Children with ADHD had lower pain thresholds than the healthy controls (P < 0.05). However, lower regional pain thresholds were observed in the ADHD group without MPH compared to both the healthy control and ADHD with MPH groups. Although pain thresholds in the ADHD with MPH group were regionally lower than in the healthy controls, low pain thresholds were found in fewer regions compared to the ADHD without MPH group. Conclusions Children with ADHD are more sensitive to pain sensation, and MPH may help normalize these individuals' pain experiences by raising pain thresholds. Families and clinicians must be aware of situations that may cause pain in children with ADHD. In addition, these children's low threshold for pain may lead them to experience it more intensely.